Selective Excitation of Polarization‐Steered Chiral Photoluminescence in Single Plasmonic Nanohelicoids. (16th April 2021) - Gao, Han; Chen, Pei‐Gang; Lo, Tsz Wing; Jin, Wei; Lei, Dangyuan
Abstract: The development of chiral photoluminescence (PL) has drawn extensive attention owing to its potential applications in optical data storage, biosensing, and displays. Due to the lack of effective synthesis methods, colloidal metal nanostructures with intrinsic chiral PL have rarely been reported. Herein, the chiral excitation and emission properties of single gold nanohelicoids (GNHs) are reported for the first time. By measuring their circular dichroism (CD) response and excitation/emission polarization‐resolved PL spectra, it is revealed that the intrinsic chirality arising from the geometric handedness of the GNHs induces the observed excitation‐polarization‐correlated chiral PL. Two models are developed to analyze the observed circular‐polarization‐steered effect: (1) a chiral PL phenomenological model quantitatively reproduces the PL dissymmetry features; (2) a chiral Purcell effect model reveals that the super‐chiral near fields in the GNHs account for the far‐field chiral responses such as the polarization‐steered chiral PL. The findings not only provide an important understanding of the physical mechanism responsible for luminescent chiral plasmonic nanostructures, but also expand the research on chiral PL‐active materials from achiral/chiral hybrid systems to metallic nanostructures with intrinsic structural chirality, thereby broadening the scope of applications in 3D chiral imaging and sensing as well as microstructure analysis. Abstract : Polarization‐steered chiral photoluminescence can be selectively excited from single plasmonic nanohelicoids with intrinsic chirality.